Minimum-time Feedforward Plus PID Control for MIMO Systems - Piccagli, Stefano; Visioli, Antonio (IFAC Proceedings Volumes, 2008)
In this paper we propose a technique for the determination of a feedforward control law to be applied to a closed-loop PID-based control system for a multi-input multi-output process in order to achieve a minimum-time transition of the outputs subject to constraints on both the control variables and the system outputs. The optimal command inputs are determined by suitably approximating the state variables and the input signals by means of Chebyshev series and by subsequently solving a constrained optimisation problem. Simulation results demonstrate the effectiveness of the methodology.